2019
DOI: 10.1016/j.ccell.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb Repressor Complex 1 Drives Double-Negative Prostate Cancer Metastasis by Coordinating Stemness and Immune Suppression

Abstract: Highlights d PRC1 promotes metastatic outgrowth by inducing expression of CCL2 d CCL2 promotes self-renewal by binding to CCR4 on prostate cancer cells d CCL2 recruits M2-like TAMs and Tregs, inducing immune suppression and angiogenesis d PRC1 inhibitor cooperates with checkpoint immunotherapy to suppress metastasis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 65 publications
5
117
0
1
Order By: Relevance
“…S14). In concordance with our data, it was recently shown that inhibition of polycomb repressor complex-1 in double-negative PCa models resulted in increased T-cell tumor infiltration, decreased immune suppressive cells and provided superior therapeutic benefit when combined with CPI(27).Identifying mechanisms driving resistance towards checkpoint immunotherapy in PCa patients remains a critical requirement. While progress has been made describing molecular events that increase response, including patients with DNA damage repair pathway defects(28,29), biallelic loss of CDK12 (30), recycling of PD-L1 in patients lacking a common mutation in SPOP(31), and inhibition of IL-23(32), the majority of patients treated with CPI remain unresponsive.…”
supporting
confidence: 89%
“…S14). In concordance with our data, it was recently shown that inhibition of polycomb repressor complex-1 in double-negative PCa models resulted in increased T-cell tumor infiltration, decreased immune suppressive cells and provided superior therapeutic benefit when combined with CPI(27).Identifying mechanisms driving resistance towards checkpoint immunotherapy in PCa patients remains a critical requirement. While progress has been made describing molecular events that increase response, including patients with DNA damage repair pathway defects(28,29), biallelic loss of CDK12 (30), recycling of PD-L1 in patients lacking a common mutation in SPOP(31), and inhibition of IL-23(32), the majority of patients treated with CPI remain unresponsive.…”
supporting
confidence: 89%
“…A summary of most recent studies addressing combination strategies between epigenetics and immune environment in PCa is depicted in Table 3 [108,[141][142][143][144][145][146][147][148][149][150][151][152]. Some studies have focused on epigenetic regulation of response to IFN, where both methylation and acetylation can be involved, as demonstrated by Dunn and collaborators [141].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Like for CTAs, decitabine also restored/induced the expression of the chemokine CXCL14, which functions as a chemoattractant for dendritic cells [145]. On the other hand, Su and coworkers [151] have focused on CCL2. In their work, they uncovered that the polycomb repressor complex 1 (PRC1) in androgen-receptor and neuroendocrine double-negative PCa is responsible for producing metastases, by regulating CCL2 expression.…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…This trend also held true for another two chemokines CCL3 and CCL4 (figure 4C, p<0.01). Tumor-derived CCL2 and CCL5 are significant indicators of early relapse and the infiltration of tumor-associated macrophages (TAMs), which contribute to cancer cell proliferation, the inflammatory microenvironment, immune evasion and angiogenesis 21–23. The proportion of TAM infiltration deduced by CIBERSORT was significantly higher in the MSI-H1 subgroup than in the MSI-H2 subgroup (online supplementary figure S3, p = 0.007, Wilcoxon test).…”
Section: Resultsmentioning
confidence: 99%